Brand identity on local malay herbal toiletries' packaging designs as potential tourism products / Siti Sarah Adam Wan and Noraziah Mohd Razali - Adam Wan, Siti Sarah; Mohd Razali, Noraziah (Faculty of Art and Design, 2019)
Herbal products are gaining popularity in the worldwide market due to their perceived medicinal values to users. Even in Malaysia, the herbal industry is increasing and the products are in high demand. The Malaysian government is now focusing on the herbal industry as new economic resources as implemented in the Ninth Malaysia Plan. This study attempts to look into the local Malay herbal toiletries' packaging designs. Through visual assessment on Malay toiletry products' packaging designs which are displayed on the market shelves, it has been discovered that a majority of these packaging designs are without any representation of the Malay identity. We argue that packaging designs of the Malay herbal toiletry products can look attractive by having Malay identity on them and consequently improving the tourists' purchasing decision. This research delves into the recommendations of packaging designs by identifying the criteria and expectation needs. In order to improve this situation, we believe that the packaging designs should adopt the Kapferer's Brand Identity Model (Kapferer, 2004) that includes physique, personality, culture, relationship reflection and self-image. It is hoped that this study will improve packaging designs of local Malay herbal toiletry products in the local market shelves by embodying the Malay identity.